TANGGUNG JAWAB BANK TERHADAP NASABAH ATAS BERKURANGNYA DANA SIMPANAN DALAM DEPOSITO - eriska (JURNAL ILMU HUKUM TOPOSANTARO, 2024)
The research method used is empirical normative research which examines primary data and secondary data. Based on the results of the study, that the implementation of halal certification of MSME products in Palu city has not been implemented evenly, because there are several MSME actors who do not yet have halal certificates. Requirements and processes for organizing halal certification of MSME products must be carried out in accordance with the mandate in the JPH Law. Meanwhile, the organizing process is divided into two paths, namely, regular and self-declaration paths. Furthermore, the JPH Law has undergone changes and additions in the Job Creation Law. The changes concern the examination and testing of halal products, deciding fatwas, issuing halal certificates, and labeling. Then, with the latest changes in regulations, the issuance of halal certificates has become the authority of BPJPH, no longer the right of MUI. Perlindungan represif antara nasabah dan bank mengacu pada upaya penegakan hukum dan tindakan yang diambil oleh pemerintah atau otoritas keuangan untuk melindungi hak dan kepentingan nasabah terhadap praktik-praktik yang merugikan dari pihak bank. Ini mencakup perlindungan terhadap kebijakan, produk, atau tindakan yang dapat merugikan nasabah secara finansial atau merugikan hak-hak mereka. Bank tidak bertanggung jawab atas berkurangnya dana simpanan dalam deposito. Bentuk tanggung jawab bank terhadap nasabah atas dana simpanan dalam deposito yang berkurang adalah tanggung jawab pegawai bank berdasarkan unsur kesalahan, bahwa pegawai bank bertanggung jawab atas setiap kerugian yang timbul pada nasabah atas kesalahan/kelalaiannya, tetapi jika nasabah dapat membuktikan bahwa bank bersalah atas kerugian nasabah. Bank wajib mengganti kerugian nasabah apabila dana deposito nasabah terbukti berkurang atau tidak sesuai dengan perjanjian yang telah disepakati dalam pembukaan deposito sebagai bentuk wanprestasi perjanjian.